Association of Temperature and Historical Dynamics of Malaria in the Republic of Korea, Including Reemergence in 1993. Issue 7 (1st July 2014) - Linthicum, Kenneth J.; Anyamba, Assaf; Killenbeck, Bradley; Lee, Won-Ja; Lee, Hee Choon S.; Klein, Terry A.; Kim, Heung-Chul; Pavlin, Julie A.; Britch, Seth C.; Small, Jennifer; Tucker, Compton J.; Gaydos, Joel C.
ABSTRACT: Plasmodium vivax malaria reemerged in the Republic of Korea in 1993 after it had been declared malaria free in 1979. Malaria rapidly increased and peaked in 2000 with 4, 142 cases with lower but variable numbers of cases reported through 2011. We examined the association of regional climate trends over the Korean Peninsula relative to malaria cases in U.S. military and Republic of Korea soldiers, veterans, and civilians from 1950 to 2011. Temperatures and anomaly trends in air temperature associated with satellite remotely sensed outgoing long-wave radiation were used to observe temporal changes. These changes, particularly increasing air temperatures, in combination with moderate rains throughout the malaria season, and distribution of malaria vectors, likely supported the 1993 reemergence and peaks in malaria incidence that occurred through 2011 by accelerating the rate of parasite development in mosquitoes and increased numbers as a result of an expansion of larval habitat, thereby increasing the vectorial capacity of Anopheles vectors. High malaria rates associated with a favorable climate were similarly observed during the Korean War. These findings support the need for increased investigations into malaria predictive models using climate-related variables.